“To Defend the Citadel of its Faith from All Assaults”: Hermann Adler and the London Society for Promoting Christianity Amongst the Jews - Ellison, Robert H. (Studies in Christian-Jewish Relations, 2018)
This article employs sermons as a lens through which to examine Jewish-Christian relations in Victorian England. It focuses primarily upon discourses preached by clergy affiliated with the London Society for Promoting Christianity Amongst the Jews, and on rebuttals delivered by Hermann Adler, a London rabbi who would go on to become Chief Rabbi of the British Empire. Attention is also given to reviews of Adler's work, and to responses to those reviews. These reviews and reviews-of-reviews are evidence that there was an active conversation taking place in the pulpit and the press; the article seeks to show that preaching is one aspect of the interfaith landscape that can be much more fully explored.